Respuesta :

The following could be a correct first step to solving the equation 4(3+x)=36

  • 12 + 4 x = 36
  • 3 + x = 9
  • (4.3) + (x.4) = 36

Step-by-step explanation:

Here we have , to that which equation fits good for next step solutions for the given equation as [tex]4(3+x)=36[/tex]:

case 1: [tex]12+4x=36[/tex] :

Yes, this equation can be obtained from [tex]4(3+x)=36[/tex] as

[tex](4.3)+(4.x) = 36[/tex]

[tex](12)+(4x) = 36[/tex]

case 2: [tex]3+x=9[/tex] :

Yes, this equation can be obtained from [tex]4(3+x)=36[/tex] as

[tex]\frac{4(3+x)}{4}=\frac{36}{4}[/tex]

[tex]3+x=\frac{36}{4}[/tex]

[tex]3+x=9[/tex]

case 3: [tex]12+x=36[/tex]:

No, not possible as  [tex]4(3+x)=36[/tex] can be written as

[tex]12+4x=36[/tex] Not as [tex]12+x=36[/tex] .

case 4: [tex]3+4x=36[/tex]:

Not possible as  [tex]4(3+x)=36[/tex] can be written as

[tex]12+4x=36[/tex] Not as [tex]3+4x=36[/tex] .

case 5: [tex]4(3+x)=144[/tex]:

Not possible as  [tex]4(3+x)=36[/tex] can be written as

[tex]4(3+x)=36[/tex] Not as   [tex]4(3+x)=144[/tex].

case 6: [tex](4.3)+(4.x)=36[/tex] :

Yes, this equation can be obtained from [tex]4(3+x)=36[/tex] as

[tex](4.3)+(4.x)=36[/tex]

ACCESS MORE